2023
DOI: 10.1136/jitc-2022-006263
|View full text |Cite|
|
Sign up to set email alerts
|

Treg-selective IL-2 starvation synergizes with CD40 activation to sustain durable responses in lymphoma models

Abstract: BackgroundRoughly half of all diffuse large B-cell lymphomas (DLBCLs) are infiltrated by large numbers of regulatory T-cells (Tregs). Although the presence of ‘effector’ Tregs in particular is associated with an inferior prognosis in patients on standard rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) immunochemotherapy, the role of this cell type during lymphoma initiation and progression is poorly understood.MethodsHere, we use tissue microarrays containing prospectively co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Stirm et al found that Tregs, in cooperation with CD40 activation, sustained responses in lymphoma models. In addition, large-scale clinical studies have shown that Treg enrichment is associated with adverse outcomes, such as multiple extranidal involvement [40,41]. These findings indicate that m 5 C is closely associated with the activation and infiltration of immune cells, which can influence the development of DLBCL by modulating immune cell regulation.…”
Section: Discussionmentioning
confidence: 92%
“…Stirm et al found that Tregs, in cooperation with CD40 activation, sustained responses in lymphoma models. In addition, large-scale clinical studies have shown that Treg enrichment is associated with adverse outcomes, such as multiple extranidal involvement [40,41]. These findings indicate that m 5 C is closely associated with the activation and infiltration of immune cells, which can influence the development of DLBCL by modulating immune cell regulation.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, in a T H 2-dominated tumor microenvironment, CD40-activated macrophages fail to acquire an anti-tumor phenotype ( Grewal and Flavell, 1998 ; Peng et al, 1998 ). Interestingly, the TME also suppresses cytotoxic T cell differentiation, while promoting regulatory T cells, suggesting that CD40L secretion might be a strategy to overcome the immunosuppressive elements of the TAM phenotype ( Stirm et al, 2023 ). These data suggest that modulating CD40 signaling can repolarize macrophages from tumor-promoting to tumor-suppressive.…”
Section: Cd40/cd40lmentioning
confidence: 99%